2020
DOI: 10.1097/as9.0000000000000023
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Surgery

Abstract: Objective: To determine if Black race is associated with worse short-term postoperative morbidity and mortality when compared to White race in a contemporary, cross-specialty-matched cohort. Background: Growing evidence suggests poorer outcomes for Black patients undergoing surgery. Methods: A retrospective analysis was conducted comprising of all patients undergoing surgery in the National Surgical Quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Racial disparities have also been demonstrated in orthopaedic surgery and other surgical specialties. The increased risk of nonhome discharge in Black and Asian patients may represent a proxy for the increased risk associated with socioeconomic factors which increase risk of postoperative complications 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Racial disparities have also been demonstrated in orthopaedic surgery and other surgical specialties. The increased risk of nonhome discharge in Black and Asian patients may represent a proxy for the increased risk associated with socioeconomic factors which increase risk of postoperative complications 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that spastic hip dysplasia is more common and more severe in higher classifications of GMFCS 30. This is particularly concerning when considering Black race is associated with 20-50% higher rates of all-cause morbidity and reoperation in the 30 days after surgery, irrespective of functional impairment 31. For further analysis, it would be helpful to identify data sources that provide GMFCS data to include in the regression model on race and risk for salvage procedures.…”
Section: Discussionmentioning
confidence: 99%
“…30 This is particularly concerning when considering Black race is associated with 20-50% higher rates of all-cause morbidity and reoperation in the 30 days after surgery, irrespective of functional impairment. 31 For further analysis, it would be helpful to identify data sources that provide GMFCS data to include in the regression model on race and risk for salvage procedures. We believe that these previous works do have some relation to our data.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in hospital discharge placement by race has been reported heavily among trauma patients (Asemota et al, 2013; Chiu et al, 2019; Fat et al, 2019). Azin and colleagues emphasize how race plays a significant role in poorer postoperative outcome (Azin et al, 2020). The findings presented and those of others highlight a need for further evaluation of structural determinants of health outcomes for victims of community violence, particularly those that can be disrupted by a policy change at the hospital-level.…”
Section: Discussionmentioning
confidence: 99%